Penerapan Model Pembelajaran Tipe Student Teams Achievement Divisions Dengan Media LKS Teka-Teki Silang Untuk Meningkatkan Hasil Belajar Siswa SMP Negeri 1 Kanatang : (Application of the Student Teams Achievement Divisions Type Learning Model Using Crossword Puzzle LKS Media to Improve Student Learning Outcomes at SMP Negeri 1 Kanatang) - Padu Ewut, Esiana; Makaborang , Yohana; Ndjoeroemana, Yohana (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The aim of this research is to provide a brief overview of the current state of research in the field of Student Teams-Achievement Divisions (STAD). In this paper, researchers will focus on a small group-based cooperative learning model, namely the Student Teams Achievement Divisions model. Researchers will also highlight recent developments in this field. The results of the research show that the use of the Student Teams Achievement Divisions learning model complete with crossword puzzle worksheet media can improve the learning outcomes of class VIII students at SMP Negeri 1 Kanatang on the subject of the human excretory system. The initial condition was that only 33% had completed and 67% had not completed, whereas in cycle I there were 43% of students who had completed, while in cycle II it increased to 83.3%. Completed and incomplete was 16.7%. Based on the results of this research, it is recommended for science teachers to try using the Student Teams Achievement Divisions model with crossword worksheet media in class VIII to improve student learning outcomes. Abstrak. Tujuan dari penelitia ini adalah untuk memberikan gambaran singkat tentang keadaan terkini penelitian di bidang Student Teams-Achievement Divisions (STAD). Dalam tulisan ini, peneliti akan fokus pada model pembelajaran kooperatif berbasis kelompok kecil adalah model Student Teams Achievement Divisions. Peneliti juga akan menyoroti perkembangan terkini di bidang ini. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran Student Teams Achievement Divisions di lengkapi media LKS Teka-Teki Silang dapat meningkatkan hasil belajar siswa kelas VIII Smp Negeri 1 Kanatang Pada Materi Sistem Ekskresi Pada Manusia. Kondisi awal hanya mencapai 33% yang tuntas dan yang tidak tuntas sebanyak 67% sedangkan pada siklus I terdapat 43% siswa tuntas sedangkan pada siklus II meningkat menjadi 83,3% yang. Tuntas dan yang tidak tuntas sebanyak 16,7%. Berdasarkan hasil penelitian ini, disarankan bagi guru IPA untuk mencoba menggunakan model Student Teams Achievement Divisions dengan media LKS Teka-Teki Silang di kelas VIII sampai meningkatkan hasil belajar siswa